1989
DOI: 10.1088/0953-4075/22/10/011
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of Au atom Rydberg states

Abstract: A beam of gold atoms was produced by heating the gold-containing material by an electro-thermal method. Two UV laser beams then irradiated the atomic beam perpendicularly, which excited the Au atoms to very high Rydberg states from their ground states (6S1/2). A high voltage pulsed electric field was then applied to the interaction region approximately 200 ns after the laser pulse, ionising the Au atoms in Rydberg states. By scanning the wavelength of the laser over a certain range, the positions of 38 energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 2 publications
1
8
0
Order By: Relevance
“…Although the infrared (IR) spectra of Au clusters are being actively studied, the atomic Au IR lines are not completely known. Indeed, while the Au spectrum was studied in various spectral domains for several decades [3][4][5][6][7][8][9], to our knowledge only one experimental work [7] concerning the IR range was reported.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the infrared (IR) spectra of Au clusters are being actively studied, the atomic Au IR lines are not completely known. Indeed, while the Au spectrum was studied in various spectral domains for several decades [3][4][5][6][7][8][9], to our knowledge only one experimental work [7] concerning the IR range was reported.…”
Section: Introductionmentioning
confidence: 99%
“…Using resonance excitation followed by electric field ionization, Ding et al [8] studied about 38 high Rydberg (5d 10 )nd 3/2 and (5d 10 )ns 1/2 levels of the Au atom. The fitted thresholds for these series gave, for the first ionization, a limit of 74409.8(3) cm −1 and 74410.0(2) cm −1 , respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed IR emission spectra of the Au atom are presented in Figure 19 at 10 µsafterthe laser shot, when the time profile of the emission intensity is maximum for all the observed lines. Although the Au spectrum has been studied in various spectral domains for several decades (Brown & Ginter, 1978;Ding et al, 1989;Dyubko et al, 2005;Ehrhardt & Davis, 1971;George et al, 1988;Jannitti et al, 1979;Platt & Sawyer, 1941), to our knowledge only one experimental study George et al (1988) concerning the studied 3-5 µmI Rr a n g ei s reported. As compared to George et al (1988) we observed several strong new Au lines in the 1800-4000 cm -1 domain.…”
Section: Results For Aumentioning
confidence: 99%
“…Brown and Ginter calculated a new value of the ionization potential: V IP = 74 408.88(17) cm −1 . Further improvements of V IP resulted from subsequent investigations carried out by laser spectroscopy [3,7,8]. In all these investigations Au atoms were excited to S, P and D Rydberg states by means of two-step or three-step resonant excitation, and the ionization threshold was determined from the convergence limits of Rydberg series.…”
Section: Introductionmentioning
confidence: 99%